MOOCS PARENTING SEBAGAI UPAYA PELIBATAN ORANGTUA PADA PENDIDIKAN ANAK INDONESIA - Mukti Amini; Siti Aisyah; Mutiara Magta; Dian Novita (Pusat Pengabdian kepada Masyarakat- LPPM Universitas Terbuka, 2023)
Various parties, especially parents, can carry out children's education. Education by parents is included in the informal channel. To properly educate children, parents need to receive adequate provisions so that parents can educate and care for their children based on their needs and the development of children. This provision can be provided in various formats, including online training packaged as Massive Open Online Courses (MOOCs) Parenting. MOOCs Parenting, prepared by the ECE-UT study program team, consists of 6 main topics: child growth and development, healthy eating, the concept of playing in children, playing time, discipline, and effective discipline. For each subject, a discussion space is provided to discuss the topic according to the time allotted. In addition, independent exercises and formative tests are also offered in each case as feedback to participants on the issues raised. At the end of the Moocs session, a competency test was given, which consisted of 20 objective questions that tested participants' mastery of the six previous topics. Participants who actively complete all issues and take competency tests will receive a certificate. In 2022, Moocs parenting has been opened starting in July 2022 and is being attended by 119 participants. Currently, some participants have been able to complete the MOOCs online training and are entitled to a certificate. At the end of the session, a MOOCs evaluation form was also prepared, which was helpful for managers in ECE-UT study programs to make improvements to Moocs Parenting from time to time.Key words: MOOCs, ParentingABSTRAKPendidikan anak dapat dilakukan oleh berbagai pihak, terutama orang tua. Pendidikan oleh orang tua ini termasuk dalam jalur informal. Agar dapat mendidik anak dengan tepat, orang tua perlu mendapat pembekalan yang memadai, agar orang tua dapat mendidik dan mengasuh anaknya berdasarkan kebutuhan dan perkembangan anak. Bekal ini dapat disediakan dalam berbagai format, antara lain melalui pelatihan daring yang dikemas dalam bentuk Massive Open Online Courses (MOOCs) Parenting. MOOCs Parenting yang disiapkan tim prodi PGPAUD UT terdiri dari 6 topik utama yaitu pertumbuhan dan perkembangan anak, makan sehat, konsep bermain pada anak, waktu bermain, disiplin, disiplin efektif. Pada setiap topik disediakan ruang diskusi untuk membahas topik sesuai waktu yang disediakan. Selain itu juga disediakan latihan mandiri dan tes formatif pada tiap topik, sebagai umpan balik pada peserta terhadap topik yang diangkat. Pada akhir sesi MOOCs diberikan uji kompetensi yang terdiri dari 20 soal objektif yang menguji penguasaan peserta terhadap keenam topik sebelumnya. Peserta yang aktif menyelesaikan semua topik dan mengerjakan uji kompetensi akan mendapatkan sertifikat. Pada tahun 2022 ini, MOOCs parenting telah dibuka mulai bulan Juli 2022, dan diikuti 115 peserta. Saat ini, sebagian peserta telah mampu menyelesaikan pelatihan daring MOOCs dan berhak mendapatkan sertifikat. Pada akhir sesi juga disiapkan form evaluasi MOOCs yang berguna bagi pengelola di prodi PGPAUD UT untuk melakukan penyempurnaan MOOCs Parenting ini dari waktu ke waktu.